Perkembangan Perbankan Indonesia: Analisis Dampak terhadap Pertumbuhan Ekonomi Regional Indonesia dan Penyebab-penyebabnya dengan Data Panel 1983- 1999 - Nasrudin, Rus'an; Soesilo, Nining I. (Jurnal Ekonomi dan Pembangunan Indonesia, 2004)
Combining regional growth model and integration of financial institution model, this paper evaluates whether intermediary development influences growth in Indonesia. Recent research has proved that not only banks development influence economic growth positively but also its exogenous components. However, there are several different assumptions during adopt this model in Indonesia. Especially regional approach is differing than national approach in growth model. The point is the existence of intermediary integration across region that causes the economic agent move freely within a nation. The data show that integration of financial intermediation was not always associated with economic growth. Only four of twenty-six provinces which proved strong influence of financial intermediation on economic growth. Labor condition and average annual wages are not exogenous variables which explain growth due to financial intermediation in Indonesia. at least during 1987-1998.